Rancang Bangun Sistem Pakar untuk Diagnosa Penyakit Mulut dengan Menggunakan Teorema Bayes Berbasis Android - Panjaitan, Muhammad Iiqbal; Rahmi, Elvika (MEANS (Media Informasi Analisa dan Sistem), 2020)
The lack of knowledge of oral health and limited sources of information causes low public awareness of oral health and also causes people to be reluctant to have their oral health checked by a doctor due to the high cost of consultation. The expert system for diagnosing oral diseases is expected to provide knowledge about the diagnosis of oral diseases, provide media for consultation on diseases of the mouth and reduce the number of consultation costs. Expert system (expert system) is a system with working principles by trying and adopting knowledge that is owned by humans and transferred to the computer, so that the computer can solve problems as usually done by experts. Bayes' Theorem is a way of finding conditional probabilities. Conditional probability is the probability of an event occurring, given that it has some relationship with one or more other events. This expert system application uses Android as the operating system. The Android-based operating system is an operating system that is open source so that it is easy to develop and optimize. The results of this study are an expert system application that can provide knowledge about the diagnosis of oral diseases, becoming a medium for consultation on oral diseases.